Perovskite single crystal material preparation and surface treatment process
Through the single crystal growth process of solvent volatilization and low-temperature inversion fusion and nBABr-assisted surface treatment technology, the problems of high surface roughness, high defect density and internal cracks of perovskite single crystal materials are solved, and the high performance and excellent resistivity of the material are achieved.
Patent Information
- Application Number
- CN202510084773.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing perovskite single crystal materials have high surface roughness, high defect density, and are prone to internal cracks during preparation, resulting in poor performance.
The single crystal growth process of solvent volatile and low-temperature inversion fusion is adopted, combined with nBABr-assisted surface treatment technology, nucleation crystallization process is regulated, internal stress of the crystal, and surface roughness is reduced through mechanical and chemical treatment.
The low surface roughness, low defect density and high resistivity of perovskite single crystal materials are achieved, avoiding the problem of internal cracks and improving the performance and application range of the material.
Smart Images

Figure CN119843364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of perovskite single crystal material preparation, in particular to a solvent volatilization and low-temperature inversion fusion single crystal growth process and nBABr-assisted surface treatment technology. Background Art
[0002] High-energy ray detection, such as X-rays and gamma rays, has important application significance in the fields of nuclear safety, medical diagnosis, safety inspection, etc. Compared with traditional semiconductor detection materials, the optoelectronic properties of perovskite single crystal materials have certain advantages, including tunable absorption spectrum range, large light absorption coefficient and excellent charge transport capacity, etc., and are considered to be one of the key materials for achieving high-sensitivity high-energy ray detection.
[0003] Although perovskite single crystal materials have excellent optoelectronic properties, the single crystals reported so far still face the following problems: (1) The surface roughness of single crystal materials is relatively high, resulting in poor contact between the functional layer and the electrode layer in the subsequent device preparation; (2) The surface defect state density of single crystal materials is relatively high, resulting in poor performance of subsequent devices; (3) Single crystal materials based on the inversion crystallization method will produce a large number of internal cracks caused by stress during the removal process. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of high surface roughness, high defect density, easy generation of internal cracks and poor performance of existing perovskite single crystal materials. The present invention provides a perovskite single crystal material and its preparation process and application. On the one hand, the nucleation and crystallization in the material growth process are regulated at low temperature to avoid the generation of internal stress in the crystal; on the other hand, the crystal surface is mechanically and chemically treated to reduce the surface roughness of the material.
[0005] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a process for preparing a perovskite single crystal material and treating the surface thereof, comprising the following steps:
[0007] S1, providing methyl ammonium bromide powder, lead bromide powder, and N, N-dimethylformamide solvent, mixing methyl ammonium bromide powder and lead bromide powder and dissolving them in N, N-dimethylformamide solvent to obtain MAPbBr of a preset concentration. 3 Precursor solution;
[0008] S2, MAPbBr 3 After the precursor solution is filtered, the solvent is evaporated and baked to obtain a bulk perovskite single crystal material;
[0009] S3, grinding and polishing the bulk perovskite single crystal material to obtain a mirror-type perovskite single crystal material;
[0010] S4, providing bromobutanol powder and isopropanol solvent, and dissolving the bromobutanol powder in the isopropanol solvent to form an nBABr solution;
[0011] S5. Soak the mirror-type perovskite single crystal material in nBABr solution for a preset time and then dry it to obtain a finished product.
[0012] Furthermore, the preset concentration in S1 is 1.6 mol / L.
[0013] Furthermore, the weight ratio of methyl ammonium bromide powder to lead bromide powder in S1 is 1:3.
[0014] Furthermore, in S2, the MAPbBr3 precursor solution is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.18 to 0.25 microns.
[0015] Furthermore, in S2, the specific operation of solvent volatilization and baking is to filter the MAPbBr 3 The precursor solution is loaded into an open glass container and placed in a variable temperature oven, and the glass sheet partially covers three-quarters of the container opening; the initial temperature of the variable temperature oven is set to 25°C, the temperature is increased by 0.5°C every 24 hours, and the oven is baked for 6 days; after the temperature reaches 28°C, the temperature is increased by 1°C every 24 hours, and the oven is baked for 2 days to obtain a bulk perovskite single crystal material.
[0016] Furthermore, the specific operation of polishing in S3 is to polish the bulk perovskite single crystal material successively using 1500 mesh, 3000 mesh, 5000 mesh, 7000 mesh, 10000 mesh and 15000 mesh sandpaper, and after each polishing, gently wipe the polished part with a dust-free cloth soaked in IPA, and use a polishing machine for mechanical fine polishing, and gently wipe the polished part with a dust-free cloth soaked in IPA, and finally obtain a mirror-type perovskite single crystal material.
[0017] Furthermore, in S4, the amount of bromobutanol powder added is 10 mg, and the amount of isopropanol solvent added is 10 mL.
[0018] Furthermore, in S5, the preset time is 10 to 20 seconds.
[0019] In a second aspect, the present invention also provides a perovskite single crystal material prepared by the above-mentioned preparation process.
[0020] In a third aspect, the present invention further provides an application based on the above-mentioned perovskite single crystal material, wherein the perovskite single crystal material is used to prepare a high-energy ray detector.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] 1. A perovskite single crystal material preparation and surface treatment process involved in the present invention, first of all, the present invention controls the solvent evaporation rate by the glass sheet ratio covering method, maintains a slower rate in the early nucleation process, and accelerates the growth rate in the subsequent crystallization process. Compared with the perovskite single crystal material prepared by the traditional solvent evaporation method, the nucleation crystallization process is more controllable, and the material grows faster. Secondly, the present invention further reduces the solubility in a controllable manner by the low-temperature inversion crystallization method and the solvent evaporation method, avoiding the problem of difficult crystal precipitation caused by the slow decrease of the solubility of the solution at low temperature and the inability of the solution to reach a saturated state. Compared with the perovskite single crystal material prepared by the traditional inversion crystallization method, the required growth temperature of the crystal is reduced from 80°C to 30°C, and at the same time, the problem of easy formation of internal cracks in the crystal when it is taken out due to the large temperature difference between the solution and the outside can be avoided. Therefore, the perovskite single crystal material prepared by the preparation process of the present invention has a higher resistivity and less defect density than the existing perovskite single crystal material, excellent performance, and superiority.
[0023] In this preparation process, the crystal is initially polished from coarse to fine by sandpaper of various mesh sizes to form a MAPbBr3 perovskite single crystal with a surface roughness of hundreds of nanometers. On this basis, a polishing machine is also used to perform more fine mechanical polishing to form a MAPbBr3 perovskite single crystal with a surface roughness of nanometers. Therefore, the perovskite single crystal material prepared by the present invention has a lower crystal surface roughness than the traditional manually polished perovskite single crystal material, which is conducive to the deposition and attachment of metal electrodes in the subsequent device preparation.
[0024] In addition, the surface of MAPbBr3 perovskite single crystal is further treated by nBABr-assisted surface treatment technology to passivate its surface defects. This surface treatment method can fill and replace defects such as halogen and cation vacancies on the surface of the crystal, forming a two-dimensional layered perovskite material with a nanometer thickness, protecting its surface, and thus solving the problem of too high surface state density of artificially polished perovskite single crystal materials.
[0025] 2. The perovskite single crystal material involved in the present invention has good material uniformity, high resistivity, low defect density and excellent performance.
[0026] 3. The application of the perovskite single crystal material involved in the present invention has a wide range of applications due to its excellent material properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the perovskite single crystal material 1 prepared in an embodiment of the present invention.
[0028] Figure 2 Schematic diagram showing the comparison of X-ray diffraction patterns of perovskite single crystal material 1 and perovskite single crystal material 2 in the experimental example of the present invention.
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0030] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. DETAILED DESCRIPTION
[0031] In a first aspect, the present invention provides a process for preparing a perovskite single crystal material and treating the surface thereof, comprising the following steps:
[0032] S1, providing methyl ammonium bromide powder, lead bromide powder, and N, N-dimethylformamide solvent, mixing methyl ammonium bromide powder and lead bromide powder and dissolving them in N, N-dimethylformamide solvent to obtain MAPbBr of a preset concentration. 3 Precursor solution;
[0033] S2, MAPbBr 3 After the precursor solution is filtered, the solvent is evaporated and baked to obtain a bulk perovskite single crystal material;
[0034] S3, grinding and polishing the bulk perovskite single crystal material to obtain a mirror-type perovskite single crystal material;
[0035] S4, providing bromobutanol powder and isopropanol solvent, and dissolving the bromobutanol powder in the isopropanol solvent to form an nBABr solution;
[0036] S5. Soak the mirror-type perovskite single crystal material in nBABr solution for a preset time and then dry it to obtain a finished product.
[0037] In certain embodiments of the present invention, the preset concentration in S1 is 1.6 mol / L.
[0038] In certain embodiments of the present invention, the weight ratio of methyl ammonium bromide powder to lead bromide powder in S1 is 1:3.
[0039] In certain embodiments of the present invention, in S2, the MAPbBr3 precursor solution is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.18 to 0.25 microns.
[0040] In certain embodiments of the present invention, the specific operation of solvent volatilization and baking in S2 is to filter the MAPbBr 3 The precursor solution is loaded into an open glass container and placed in a variable temperature oven, and the glass sheet partially covers three-quarters of the container opening; the initial temperature of the variable temperature oven is set to 25°C, the temperature is increased by 0.5°C every 24 hours, and the oven is baked for 6 days; after the temperature reaches 28°C, the temperature is increased by 1°C every 24 hours, and the oven is baked for 2 days to obtain a bulk perovskite single crystal material.
[0041] It is understandable that the solvent evaporation rate is regulated by the glass sheet ratio covering method, a slower rate is maintained in the early nucleation process, and the growth rate is accelerated in the subsequent crystallization process. Compared with the perovskite single crystal material prepared by the traditional solvent evaporation method, the nucleation crystallization process is more controllable, and the material grows fast. Secondly, the present invention further reduces the solubility in a controllable manner by the low-temperature inversion crystallization method in conjunction with the solvent evaporation method, thereby avoiding the problem of difficult precipitation of crystals due to the slow decrease in solution solubility at low temperatures and the inability of the solution to reach a saturated state. Compared with the perovskite single crystal material prepared by the traditional inversion crystallization method, the required growth temperature of the crystal is reduced from 80°C to 30°C, and at the same time, the problem of easy formation of internal cracks in the crystal when it is taken out due to the large temperature difference between the solution and the outside can be avoided. Therefore, the perovskite single crystal material prepared by the preparation process of the present invention has a higher resistivity and less defect density than the existing perovskite single crystal material, and has excellent performance and superiority.
[0042] In certain embodiments of the present invention, the specific operation of polishing in S3 is to polish the bulk perovskite single crystal material successively using 1500 mesh, 3000 mesh, 5000 mesh, 7000 mesh, 10000 mesh and 15000 mesh sandpaper, and after each polishing, gently wipe the polished part with a dust-free cloth soaked in IPA, and use a polishing machine for mechanical fine polishing, and gently wipe the polished part with a dust-free cloth soaked in IPA, and finally obtain a mirror-type perovskite single crystal material.
[0043] In certain embodiments of the present invention, mechanical fine polishing is performed using a polishing machine, specifically, using a polishing machine equipped with a soft wool flannel cloth to perform mechanical fine polishing on the above-mentioned crystal, and gently wiping the polished part with a dust-free cloth soaked in IPA to obtain a mirror-type perovskite single crystal material.
[0044] It should be understood that the crystal is initially polished from coarse to fine by sandpaper of various mesh sizes to form a MAPbBr3 perovskite single crystal with a surface roughness of hundreds of nanometers. On this basis, a polishing machine is also used in combination to perform more fine mechanical polishing to form a MAPbBr3 perovskite single crystal with a surface roughness of nanometers. Therefore, the perovskite single crystal material prepared by the present invention has a lower crystal surface roughness than the traditional manually polished perovskite single crystal material, which is conducive to the deposition and attachment of metal electrodes in the subsequent device preparation.
[0045] In certain embodiments of the present invention, in S4, the amount of bromobutanol powder added is 10 mg, and the amount of isopropanol solvent added is 10 mL. The surface of the MAPbBr3 perovskite single crystal is further treated by nBABr-assisted surface treatment technology to passivate its surface defects. This surface treatment method can fill and replace defects such as halogen and cation vacancies on the surface of its crystal, forming a two-dimensional layered perovskite material with a nanometer thickness, protecting its surface, thereby solving the problem of excessive surface state density of artificially polished perovskite single crystal materials.
[0046] In some embodiments of the present invention, in S5, the preset time is 10 to 20 seconds.
[0047] In a second aspect, the present invention also provides a perovskite single crystal material prepared by the above-mentioned preparation process, which has good material uniformity, high resistivity, low defect density and excellent performance.
[0048] In a third aspect, the present invention further provides an application based on the above-mentioned perovskite single crystal material, wherein the perovskite single crystal material is used to prepare a high-energy ray detector. Due to the excellent performance of the perovskite single crystal material of the present invention, it has a wide range of applications.
[0049] Example 1
[0050] In this embodiment, the specific operations are:
[0051] (1) Weigh 1791.52 mg of methylammonium bromide (MABr) powder and 5872.16 mg of lead bromide (PbBr) powder respectively. 2 ) powder, weighing error is less than 0.03%;
[0052] (2) The weighed MABr and PbBr 2 The powders were mixed and dissolved in 10 mL of N,N-dimethylformamide (DMF) solvent;
[0053] (3) Stir the above solution until the solution becomes clear to form a MAPbBr solution with a molar concentration of 1.6 mol / L. 3 Precursor solution;
[0054] (4) The MAPbBr 3 The solution is filtered and dispensed into flat-bottomed open glass containers;
[0055] (5) will contain MAPbBr 3 The open glass container of the solution is placed in a variable temperature oven, and a glass sheet partially covers three-quarters of the container opening;
[0056] (6) The initial temperature of the variable temperature oven was set to 25°C, and the temperature was increased by 0.5°C every 24 hours for 6 days;
[0057] (7) After the temperature reaches 28°C, increase the temperature by 1°C every 24 hours for 2 days;
[0058] (8) Take out the grown bulk MAPbBr 3 Perovskite single crystal material, wipe it gently with a dust-free cloth and keep it dry;
[0059] (9) using sandpapers of 1500 mesh, 3000 mesh, 5000 mesh, 7000 mesh, 10000 mesh and 15000 mesh to polish the crystal successively, and after each polishing, gently wipe the polished part with a dust-free cloth soaked in IPA;
[0060] (10) The crystal was finely polished using a polishing machine equipped with soft wool flannel, and the polished portion was gently wiped with a dust-free cloth soaked in IPA to obtain a mirror-type MAPbBr 3 Perovskite single crystal;
[0061] (11) Weigh 10 mg of bromobutyl alcohol (nBABr) powder, dissolve it in 10 mL of isopropyl alcohol (IPA) solvent, and stir it until the solution becomes clear to form an nBABr solution; immerse the polished and cleaned perovskite single crystal material in the nBABr solution as a whole, take out the crystal after immersion for 15 seconds, and blow dry it with nitrogen to prepare the perovskite single crystal material 1.
[0062] Comparative Example 1
[0063] In this comparative example, the specific operations are:
[0064] (1) Weigh 1791.52 mg of methylammonium bromide (MABr) powder and 5872.16 mg of lead bromide (PbBr) powder respectively. 2 ) powder, weighing error is less than 0.03%;
[0065] (2) The weighed MABr and PbBr 2The powders were mixed and dissolved in 10 mL of N,N-dimethylformamide (DMF) solvent;
[0066] (3) Stir the above solution until the solution becomes clear to form a MAPbBr solution with a molar concentration of 1.6 mol / L. 3 Precursor solution;
[0067] (4) filtering the MAPbBr3 solution using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm and dispensing the solution into a flat-bottomed open glass container;
[0068] (5) placing the open glass container containing the MAPbBr3 solution in a variable temperature oven, and partially covering three quarters of the container opening with a glass sheet;
[0069] (6) The initial temperature of the variable temperature oven was set to 25°C, and the temperature was increased by 0.5°C every 24 hours for 6 days;
[0070] (7) After the temperature reaches 28°C, increase the temperature by 1°C every 24 hours for 2 days;
[0071] (8) Take out the grown bulk MAPbBr3 perovskite single crystal material and wipe it gently with a dust-free cloth to keep it dry;
[0072] (9) using sandpapers of 1500 mesh, 3000 mesh, 5000 mesh, 7000 mesh, 10000 mesh and 15000 mesh to polish the crystal successively, and after each polishing, gently wipe the polished part with a dust-free cloth soaked in IPA;
[0073] (10) The crystal was finely polished using a polishing machine equipped with soft wool flannel cloth, and the polished portion was gently wiped with a dust-free cloth soaked in IPA to prepare a perovskite single crystal material 2.
[0074] Experimental Example 1 Performance Characterization of Perovskite Single Crystal Material 1 and Perovskite Single Crystal Material 2
[0075] 1.1 Test operation
[0076] The crystal quality of the perovskite single crystal material 1 prepared in Example 1 and the perovskite single crystal material 2 prepared in Comparative Example 1 was tested using an X-ray diffractometer (XRD). Figure 2 .
[0077] 1.2 Results Analysis
[0078] See also Figure 2It can be seen (the ordinate is intensity representing the intensity, and the abscissa is 2Theta representing the angle) that the perovskite single crystal material 1 prepared in Example 1 has better crystallization quality and lower surface state density.
[0079] The above embodiment is only one implementation of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A perovskite single crystal material preparation and surface treatment process, characterized in that: The following steps are involved: S1. Provide methyl ammonium bromide powder, lead bromide powder, and N,N-dimethylformamide solvent, mix the methyl ammonium bromide powder and lead bromide powder and dissolve them in N,N-dimethylformamide solvent to obtain a MAPbBr3 precursor solution of a preset concentration; S2, filtering the MAPbBr3 precursor solution, evaporating the solvent, and baking to obtain a bulk perovskite single crystal material; S3, grinding and polishing the bulk perovskite single crystal material to obtain a mirror-type perovskite single crystal material; S4, providing bromobutanol powder and isopropanol solvent, and dissolving the bromobutanol powder in the isopropanol solvent to form an nBABr solution; S5. Soak the mirror-type perovskite single crystal material in nBABr solution for a preset time and then dry it to obtain a finished product.
2. A perovskite single crystal material preparation and surface treatment process according to claim 1, characterized in that: The preset concentration in S1 is 1.6 mol / L.
3. The process for preparing and surface treating a perovskite single crystal material according to claim 1, characterized in that: The weight ratio of methyl ammonium bromide powder to lead bromide powder in S1 is 1:
3.
4. The process for preparing and surface treating a perovskite single crystal material according to claim 1, characterized in that: In the above-mentioned S2, the MAPbBr3 precursor solution is filtered using a polytetrafluoroethylene filter membrane with a pore size of 0.18 to 0.25 microns.
5. The process for preparing and surface treating a perovskite single crystal material according to claim 1, characterized in that: In S2, the specific operations of solvent volatilization and baking are as follows: the filtered MAPbBr3 precursor solution is placed in an open glass container and placed in a variable temperature oven, and the glass sheet partially covers three quarters of the container opening; the initial temperature of the variable temperature oven is set to 25°C, the temperature is increased by 0.5°C every 24 hours, and baking is performed for 6 days; after the temperature reaches 28°C, the temperature is increased by 1°C every 24 hours, and baking is performed for 2 days to obtain a bulk perovskite single crystal material.
6. The process for preparing and surface treating a perovskite single crystal material according to claim 1, characterized in that: The specific operation of polishing in S3 is to polish the bulk perovskite single crystal material successively using 1500 mesh, 3000 mesh, 5000 mesh, 7000 mesh, 10000 mesh and 15000 mesh sandpaper, and after each polishing, gently wipe the polished part with a dust-free cloth soaked in IPA, and use a polishing machine for mechanical fine polishing, and gently wipe the polished part with a dust-free cloth soaked in IPA, and finally obtain a mirror-type perovskite single crystal material.
7. The process for preparing and surface treating a perovskite single crystal material according to claim 1, characterized in that: In the S4, the added amount of bromobutanol powder is 10 mg, and the added amount of isopropanol solvent is 10 mL.
8. The process for preparing and surface treating a perovskite single crystal material according to claim 1, characterized in that: In S5, the preset time is 10 to 20 seconds.
9. A perovskite single crystal material prepared by the preparation process according to any one of claims 1 to 7.
10. An application of the perovskite single crystal material according to claim 9, characterized in that: The perovskite single crystal material is used for preparing high-energy ray detectors.